The coordinates of the point on the parabola 24xy which is nearest to the circle
\[{{(x-3)}^{2}}+{{y}^{2}}=1\] are:
(a) (0,0)
(b) (2,1)
(c) (2,1)
(d) (4,4)
Answer
Verified
512.4k+ views
Hint: To find the coordinates of the point on the parabola which has the least
distance from the circle, we will find the distance between the centre of the circle and any
point on the parabola taken in parametric form. Then, we will differentiate that distance and
equate it to zero to get the coordinates of the point which is at minimum distance from the
circle.
We have a parabola\[{{x}^{2}}=4y\] and a circle\[{{(x-3)}^{2}}+{{y}^{2}}=1\]. We want to find
the coordinates of the point on the parabola which has the least distance from the circle.
We know that any general point on the parabola of the
form\[{{x}^{2}}=4ay\]is\[(2at,a{{t}^{2}})\].
By substituting\[a=1\], we have the point on our parabola as\[(2t,{{t}^{2}})\].
We know that a circle of the form\[{{(x-h)}^{2}}+{{(y-k)}^{2}}={{r}^{2}}\]has centre\[(h,k)\].
Thus the centre of the circle\[{{(x-3)}^{2}}+{{y}^{2}}=1\]is\[(3,0)\].
We know that the distance between any two points \[({{x}_{1}},{{y}_{1}})\] and \[({{x}_{2}},{{y}_{2}})\] is \[\sqrt{{({x_1}-{x_2})}^2+{({y_1}-{y_2})}^2}\].
Substituting \[{{x}_{1}}=2t,{{y}_{1}}={{t}^{2}},{{x}_{2}}=3,{{y}_{2}}=0\] in the above formula,
we get the distance between the points to be\[\sqrt{{{(2t-3)}^{2}}+{{t}^{4}}}\].
We know that to find the minimum value of a function\[f(x)\], we have\[\dfrac{df(x)}{dx}=0\].
So, we will differentiate our function \[\sqrt{{{(2t-3)}^{2}}+{{t}^{4}}}\] with respect to\[t\].
Thus, we get
\[\Rightarrow \dfrac{d}{dt}\sqrt{{{(2t-3)}^{2}}+{{t}^{4}}}=\dfrac{1}{2\sqrt{{{(2t-3)}^{2}}+{{t}^{4}}}}\{2(2t-3)2+
4{{t}^{3}}\}=0\]
\[\begin{align}
& \Rightarrow 4(2t-3)+4{{t}^{3}}=0 \\
& \Rightarrow 8t-12+4{{t}^{3}}=0 \\
\end{align}\]
We will now factorize the above equation. Add and subtract\[4{{t}^{2}}\]from the equation.
Thus we have\[4{{t}^{3}}+8t-12=4{{t}^{3}}-4{{t}^{2}}+4{{t}^{2}}+8t-12\].
\[\begin{align}
& \Rightarrow 4{{t}^{3}}-4{{t}^{2}}+4{{t}^{2}}+8t-12=0 \\
& \Rightarrow 4{{t}^{2}}(t-1)+4({{t}^{2}}+2t-3)=0 \\
& \Rightarrow 4{{t}^{2}}(t-1)+4({{t}^{2}}+3t-t-3)=0 \\
& \Rightarrow 4{{t}^{2}}(t-1)+4(t(t+3)-1(t+3))=0 \\
& \Rightarrow 4{{t}^{2}}(t-1)+4(t-1)(t+3)=0 \\
& \Rightarrow 4(t-1)({{t}^{2}}+t+3)=0 \\
\end{align}\]
We observe that\[t=1\]satisfies the equation and the equation\[{{t}^{2}}+t+3\]has no real
roots.
Substituting the value of\[t\]in the point\[(2t,{{t}^{2}})\], we get\[(2,1)\].
So, the point on the parabola which is at minimum distance from the circle is (2,1).
Hence, the correct answer is \[(2,1)\].
Note: We can also solve this question by finding the foot of perpendicular from any general
point on parabola to the circle and then differentiating the distance between the foot of
perpendicular on circle and point on parabola and equating it to zero.
distance from the circle, we will find the distance between the centre of the circle and any
point on the parabola taken in parametric form. Then, we will differentiate that distance and
equate it to zero to get the coordinates of the point which is at minimum distance from the
circle.
We have a parabola\[{{x}^{2}}=4y\] and a circle\[{{(x-3)}^{2}}+{{y}^{2}}=1\]. We want to find
the coordinates of the point on the parabola which has the least distance from the circle.
We know that any general point on the parabola of the
form\[{{x}^{2}}=4ay\]is\[(2at,a{{t}^{2}})\].
By substituting\[a=1\], we have the point on our parabola as\[(2t,{{t}^{2}})\].
We know that a circle of the form\[{{(x-h)}^{2}}+{{(y-k)}^{2}}={{r}^{2}}\]has centre\[(h,k)\].
Thus the centre of the circle\[{{(x-3)}^{2}}+{{y}^{2}}=1\]is\[(3,0)\].
We know that the distance between any two points \[({{x}_{1}},{{y}_{1}})\] and \[({{x}_{2}},{{y}_{2}})\] is \[\sqrt{{({x_1}-{x_2})}^2+{({y_1}-{y_2})}^2}\].
Substituting \[{{x}_{1}}=2t,{{y}_{1}}={{t}^{2}},{{x}_{2}}=3,{{y}_{2}}=0\] in the above formula,
we get the distance between the points to be\[\sqrt{{{(2t-3)}^{2}}+{{t}^{4}}}\].
We know that to find the minimum value of a function\[f(x)\], we have\[\dfrac{df(x)}{dx}=0\].
So, we will differentiate our function \[\sqrt{{{(2t-3)}^{2}}+{{t}^{4}}}\] with respect to\[t\].
Thus, we get
\[\Rightarrow \dfrac{d}{dt}\sqrt{{{(2t-3)}^{2}}+{{t}^{4}}}=\dfrac{1}{2\sqrt{{{(2t-3)}^{2}}+{{t}^{4}}}}\{2(2t-3)2+
4{{t}^{3}}\}=0\]
\[\begin{align}
& \Rightarrow 4(2t-3)+4{{t}^{3}}=0 \\
& \Rightarrow 8t-12+4{{t}^{3}}=0 \\
\end{align}\]
We will now factorize the above equation. Add and subtract\[4{{t}^{2}}\]from the equation.
Thus we have\[4{{t}^{3}}+8t-12=4{{t}^{3}}-4{{t}^{2}}+4{{t}^{2}}+8t-12\].
\[\begin{align}
& \Rightarrow 4{{t}^{3}}-4{{t}^{2}}+4{{t}^{2}}+8t-12=0 \\
& \Rightarrow 4{{t}^{2}}(t-1)+4({{t}^{2}}+2t-3)=0 \\
& \Rightarrow 4{{t}^{2}}(t-1)+4({{t}^{2}}+3t-t-3)=0 \\
& \Rightarrow 4{{t}^{2}}(t-1)+4(t(t+3)-1(t+3))=0 \\
& \Rightarrow 4{{t}^{2}}(t-1)+4(t-1)(t+3)=0 \\
& \Rightarrow 4(t-1)({{t}^{2}}+t+3)=0 \\
\end{align}\]
We observe that\[t=1\]satisfies the equation and the equation\[{{t}^{2}}+t+3\]has no real
roots.
Substituting the value of\[t\]in the point\[(2t,{{t}^{2}})\], we get\[(2,1)\].
So, the point on the parabola which is at minimum distance from the circle is (2,1).
Hence, the correct answer is \[(2,1)\].
Note: We can also solve this question by finding the foot of perpendicular from any general
point on parabola to the circle and then differentiating the distance between the foot of
perpendicular on circle and point on parabola and equating it to zero.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
The correct order of melting point of 14th group elements class 11 chemistry CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE